Clinical Characteristics and Pathogenic Gene Identification in Chinese Patients With Paget’s Disease of Bone - Tao, Xiaohui; Liu, Li; Yang, Xingguang; Wei, Zhe; Chen, Zhongzhong; Zhang, Ge; Zhang, Zhenlin; Yue, Hua (Frontiers in Endocrinology, 2022)
Objective To evaluate the clinical features of sporadic Paget’s disease of bone (PDB) in China and further explore the underlying genetic abnormalities of the disease. Methods Clinical characteristics, biochemical indices, bone turnover markers and radiographic examinations of the patients were collected. Genomic DNA was extracted from peripheral blood and whole-exome sequencing was carried out to identify the potential pathogenic genes. The pathogenicity of the variants was thereafter investigated by bioinformatics analysis. Results A total of 50 patients (57.20 ± 15.52 years, male/female: 1.63: 1) with PDB were included and the mean onset age was 48.34 years (48.34 ± 17.24 years). 94.0% of the patients exhibited symptomatic patterns described as bone pain (86.0%), elevated skin temperature at the lesion site (26.0%), bone deformity (22.0%) and local swelling (18.0%). The most frequently involved lesion sites were pelvis (52.0%), femur (42.0%), tibia (28.0%), skull (28.0%) and spine (18.0%), respectively. Additionally, 40.0% of them accompanied with osteoarthritis, 14.0% with pathological fractures, and the misdiagnosis rate of PDB was as high as 36.0%. Serum level of alkaline phosphatase was significantly increased, with the mean value of 284.00 U/L (quartiles, 177.00-595.00 U/L). Two heterozygous missense mutations of SQSTM1 gene (c.1211T>C, M404T) and one novel heterozygous missense mutation in HNRNPA2B1 gene (c.989C>T, p. P330L) were identified in our study. Moreover, several potential disease-causing genes were detected and markedly enriched in the pathways of neurodegeneration (including WNT16, RYR3 and RYR1 genes) and amyotrophic lateral sclerosis (ALS, including NUP205, CAPN2, and NUP214 genes). Conclusion In contrast to Western patients, Chinese patients have an earlier onset age, more severe symptoms, and lower frequency of SQSTM1 gene mutation (4.0%). Moreover, a novel heterozygous missense mutation in HNRNPA2B1 gene was identified in one male patient with isolated bone phenotype. As for other genetic factors, it was indicated that WNT16, RYR3, RYR1, NUP205, CAPN2 and NUP214 genes may be potential pathogenic genes, pathways of neurodegeneration and ALS may play a vital role in the pathogenesis of PDB.